Plasmid-mediated quinolone resistance in expanded spectrum beta lactamase producing enterobacteriaceae in Morocco - Bouchakour, Mohammed; Zerouali, Khalid; Gros Claude, Jean David Perrier; Amarouch, Hamid; El Mdaghri, Naima; Courvalin, Patrice; Timinouni, Mohammed (The Journal of Infection in Developing Countries, 2010)
Introduction: Although independently acquired, plasmid-mediated quinolone resistance appears to be linked with extended-spectrum or AmpC-type beta-lactamases. Since no data are available in African countries, the prevalence of qnr genes at the University Hospital Ibn Rochd, Casablanca, Morocco, was investigated. Methodology: Between October 2006 and March 2007, the following 39 randomly selected non-duplicate Enterobacteriaceae producing an extended-spectrum beta-lactamase (ESBL), representing 20% of ESBL strains with respect to species and ward origin, were collected: Escherichia coli (n = 16); Klebsiella spp (n = 14); Enterobacter cloacae (n = 8); Proteus mirabilis (n = 1). Antibiotic susceptibility testing was performed according to CLSI guidelines. ESBL detection was performed by the double disc diffusion test. A multiplex PCR was conducted to detect qnrA, qnrB and qnrS genes that were confirmed by sequencing of the PCR product. Results: The estimated overall prevalence of qnr reached 36% (n = 14; qnrA, 10.25%; qnrB, 23.07%; qnrS, 2.56%). Genes were identified in E. coli, Klebsiella and Enterobacter with a respective prevalence of 18.7%, 50% and 62.5%. The qnr genes were detected in nine wards and qnrA1, qnrB1-B2-B4 and qnrS1 variants were identified. Three genes were identified among nalidixic acid susceptible strains (n = 6); three of those were also susceptible to ciprofloxacin. Among nalidixic acid and ciprofloxacin resistant strains, all strains had qnrB. Conclusions: This study highlights the high prevalence of qnr genes among ESBL strains in the Ibn Rochd CHU, Casablanca. Moreover, qnr were present in quinolone-susceptible strains which could lead to in vivo selection of ciprofloxacin-resistant strains.